Unveiling the post extraction experience–diverse patient perspectives: a descriptive study - Rani, Lotavath Jhansi; M., Veeresh; Raj S., Shanthosh; E., Himasagar; S., Periyasamy (International Journal Of Community Medicine And Public Health, 2025)
Background: Dental extractions are routine procedures in clinical dentistry, often accompanied by postoperative pain and discomfort. Understanding patient experiences during this period is essential to improve care and recovery outcomes. This study aimed to assess the post-extraction experiences of adult patients, with a focus on pain, discomfort, bleeding, and overall satisfaction, to identify trends and guide enhancements in postoperative management. Methods: A descriptive study was carried out among 150 adult patients undergoing scheduled dental extractions at ESIC Medical College and Hospital, Chennai. Participants were selected based on predefined inclusion criteria and completed a structured, self-administered questionnaire. The tool gathered demographic data and responses related to pain, swelling, bleeding, and satisfaction during and after the procedure. Data were analyzed using SPSS v.25.0, applying both descriptive and inferential statistics, with significance set at p<0.05. Results: The sample had a balanced gender distribution (48.7% males, 51.3% females) and varied age groups. Pain was the most commonly reported symptom (80%), followed by swelling (12%). Most patients (94%) felt comfortable during the extraction, and 66% reported that the procedure was quick. Postoperatively, 78% experienced mild bleeding, 19.3% moderate, and 2.7% severe bleeding. Additionally, 13.3% reported post-extraction biting injuries. Pain relief measures were largely considered effective, with only a minority requiring further interventions. Conclusions: In conclusion, the findings demonstrate that most patients experience mild to moderate postoperative symptoms, managed effectively through current clinical practices. The results emphasize the need for consistent, patient-centered pain management protocols and suggest further research on long-term recovery outcomes.